2022
DOI: 10.3390/md20030166
|View full text |Cite
|
Sign up to set email alerts
|

First Identification of 12β-Deoxygonyautoxin 5 (12α-Gonyautoxinol 5) in the Cyanobacterium Dolichospermum circinale (TA04) and 12β-Deoxysaxitoxin (12α-Saxitoxinol) in D. circinale (TA04) and the Dinoflagellate Alexandrium pacificum (Group IV) (120518KureAC)

Abstract: Saxitoxin and its analogues, paralytic shellfish toxins (PSTs), are potent and specific voltage-gated sodium channel blockers. These toxins are produced by some species of freshwater cyanobacteria and marine dinoflagellates. We previously identified several biosynthetic intermediates of PSTs, as well as new analogues, from such organisms and proposed the biosynthetic and metabolic pathways of PSTs. In this study, 12β-deoxygonyautoxin 5 (12α-gonyautoxinol 5 = gonyautoxin 5-12(R)-ol) was identified in the freshw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…A series of 12β-deoxy (= α-saxitoxinol)-type STX analogues have been identified in toxic dinoflagellates and/or a cyanobacterium, including 12β-deoxy-GTX2/3, [27] 12β-d-dcSTX (21) [28,29] and 12β-d-STX ( 22); [28] in this study, we also found 12β-d-doSTX (3). Since 12β-deoxy type (α-saxitoxinol-type) STX analogues were not converted to ketone by SxtT, [20] these 12β-deoxy analogues may be shunt products, otherwise, an unidentified enzyme may have converted them to ketones.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A series of 12β-deoxy (= α-saxitoxinol)-type STX analogues have been identified in toxic dinoflagellates and/or a cyanobacterium, including 12β-deoxy-GTX2/3, [27] 12β-d-dcSTX (21) [28,29] and 12β-d-STX ( 22); [28] in this study, we also found 12β-d-doSTX (3). Since 12β-deoxy type (α-saxitoxinol-type) STX analogues were not converted to ketone by SxtT, [20] these 12β-deoxy analogues may be shunt products, otherwise, an unidentified enzyme may have converted them to ketones.…”
Section: Discussionsupporting
confidence: 63%
“…The peaks of synthetic 5 ( m/z 241.1407±0.011) and 12β‐deoxy‐decarbamoylSTX (12β‐d‐dcSTX) ( 21 ) were separated from each other (21.3, 24.4 min) in the EIC (Figure 6a, b). 12β‐d‐dcSTX ( 21 ) has the same molecular formula as that of 5 , which was previously identified in the cyanobacterium [28] and dinoflagellates [29] . The peaks of 5 and 21 (21.5, 24.2 min), for which the MSMS spectra were almost identical to those of the synthetic compounds, were detected in the spectrum of D. circinale (TA04) (Figure 6c), suggesting that 5 is also present in this toxic cyanobacterium as well as the dinoflagellate.…”
Section: Resultsmentioning
confidence: 63%
“…The final new compound reported from dinoflagellates was a saxitoxin congener 874 from Alexandrium pacifichem ; 312 the structure of a maitotoxin congener was only partially characterised and proposed using MS and NMR data and consequently is not shown here. 313 …”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%